2013
DOI: 10.1016/j.celrep.2013.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of LINE-1 and Alu/SVA Retrotransposition by Aicardi-Goutières Syndrome-Related SAMHD1

Abstract: SUMMARY Long interspersed elements 1 (LINE-1) occupy at least 17% of the human genome and are its only active autonomous retrotransposons. However, the host factors that regulate LINE-1 retrotransposition are not fully understood. Here, we demonstrate that the Aicardi-Goutières syndrome gene product SAMHD1, recently revealed to be an inhibitor of HIV/simian immunodeficiency virus (SIV) infectivity and neutralized by the viral Vpx protein, is also a potent regulator of LINE-1 and LINE-1-mediated Alu/SVA retrotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
221
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 182 publications
(229 citation statements)
references
References 59 publications
5
221
3
Order By: Relevance
“…We have recently observed that the human SAMHD1 protein is a potent suppressor of LINE-1 activity 31 . To determine whether tetramer formation is also important for LINE-1 inhibition, we compared the functional activity of SAMHD1c 0 and SAMHD1c against LINE-1, using a well-established reporter system in HEK293T cells [32][33][34] .…”
Section: Articlementioning
confidence: 99%
“…We have recently observed that the human SAMHD1 protein is a potent suppressor of LINE-1 activity 31 . To determine whether tetramer formation is also important for LINE-1 inhibition, we compared the functional activity of SAMHD1c 0 and SAMHD1c against LINE-1, using a well-established reporter system in HEK293T cells [32][33][34] .…”
Section: Articlementioning
confidence: 99%
“…This mechanism of inhibition at least partially explains the decrease in LINE-1 ORF2 when SAMHD1 is overexpressed and drives sequestration of LNE-1 RNA in stress granules. 29,30 We also note that SAMHD1 specifically reduces the level of ORF2p but not ORF1p. 30 This is because the translation initiation of ORF2p is different from that of ORF1p.…”
mentioning
confidence: 99%
“…29,30 We also note that SAMHD1 specifically reduces the level of ORF2p but not ORF1p. 30 This is because the translation initiation of ORF2p is different from that of ORF1p. Since the inter-ORF spacer is dispensable for ORF2p translation, the translation of ORF2p most likely relies on the re-activation of ribosome that finishes the translation of ORF1p but has not dissociated from LINE-1 RNA.…”
mentioning
confidence: 99%
See 2 more Smart Citations